Motivasi, Biaya, Dan Lama Pendidikan dan Minat Mahasiswa Akuntansi Untuk Melanjutkan Pendidikan Magister Akuntansi - Suriastra, Gede Eka Prasetya Putra; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p19, 2022)
The purpose of the study was to determine the effect of motivation, education costs, and length of education on the interest of accounting students to continue their Masters in Accounting Education during the covid-19 pandemic. The research was conducted at the Faculty of Economics and Business, Udayana University. The total population is 535 students and the number of samples is 85, with non-probability sampling method using purposive sampling technique. Data was collected by means of a questionnaire. The data collected were analyzed using multiple linear regression analysis techniques. The results showed that quality, career, and economic motivation had a positive effect, while the cost of education and length of education had a negative effect on the interest of accounting students to continue their Master of Accounting Education during the COVID-19 pandemic. Keywords: Motivation; Education Cost; Length of Education; Interest in Continuing Master in Accounting.